Oxone-acetone mediated syn-dioxygenation of benzo-fused olefins - Phatake, Ravindra S.; Ramana, Chepuri V. (Tetrahedron Letters, 2015)
The oxone-acetone combination well established for olefin epoxidation has been demonstrated to be a practical reagent for the syn-dioxygenation (resulting in 1,3-dioxolanes) of indenes and dihydronaphthalenes. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Dihydronaphthalene; Dioxygenation; Indene; Oxone